Hubungan antara Penggunaan Google Classroom dengan Hasil Belajar Siswa - Dhila Nurul Azmi; R Alpha Amirrachman; Sutrisno Sadji Evenddy (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2021)
The present study aims to investigate the relationship between the use of google classroom and English learning outcomes and describe the use the google classroom and English learning at the seventh grade of SMPN 3 Cisauk. The present study utilizes a sampling technique enclosing 184 samples from 342 populations of seventh graders. Data was collected using instrument adoptions. The applied method was a survey method with a quantitative approach and ex post facto. The result of the data analysis show that the test of normality is 0,017 <0,05. The analysis was a significant positive correlation between the two variables with a correlation value of r=0,248 and coefficient of determination r2=0,061 or the contribution to the use of Google Classroom and English learning outcomes is 6,1%. The use of Google Classroom with a mean value of 91.07 is categorized as high and learning outcomes with a mean value of 84.79 are categorized as high. The results of present study suggest that the use of Google Classroom has a positive effect on the English learning outcomes of the participants.